Effects of different edge contacts on the photocatalytic and optical properties of blue phosphorene/arsenene lateral heterostructures. (21st June 2021) - Li, Shaofei; Lin, Long; Luo, Wen; Yao, Linwei; Shi, Zhengguang; Xie, Kun; Sun, Jingwen; Yu, Weiyang; Zhang, Zhanying
Abstract: Recent advances in the synthesis and characterization techniques of atomic-scale thicknesses of crystals have enabled the fabrication of various two-dimensional lateral heterostructures (LHSs). In this paper, we systematically investigate the geometrical structures, electronic properties, band alignments, and optical properties of phosphorene/arsenene LHSs using first-principles calculations based on density functional theory. First, we constructed four stable phosphorene/arsenene LHSs with different edge contacts, named A–Z, Z–A, A–A and Z–Z phosphorene/arsenene LHSs. We then investigated the electronic structures of the different edge contacts. Interestingly, the calculated electron localization functions show that the most stable six-membered rings and previously reported five-membered and seven-membered rings are formed at the interface of the blue phosphorene/arsenene LHSs. Moreover, the band edge alignments and optical absorption properties show that A–A and Z–A phosphorene/arsenene LHSs have band-edge conditions suitable for photocatalytic water decomposition, which provides a possibility for their application in the area of photocatalytic water decomposition. These results provide a route for applications of these heterostructures in future optoelectronic and semiconductor devices, and also pave the way for the design of new blue phosphorene/arsenene LHSs and the exploration of their potential applications in optoelectronic devices.